Pengaruh Produk, Harga dan Tempat Terhadap Keputusan Pembelian Produk Tomoro Coffe Pada Masyarakat Sumbawa - Suryani, Aryani; Fietroh, Muhammad Nur (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of Product, Price, and Place on the purchase decisions of Tomoro Coffee products among the people of Sumbawa Regency. The cultural shift of coffee consumption from a functional need to a modern lifestyle has contributed to intense competition in the coffee shop industry, including in developing regions such as Sumbawa. Tomoro Coffee has emerged as a new brand with an aggressive pricing strategy, claimed premium product quality, and strategically located outlets. This research employs a quantitative approach using a survey method involving 100 respondents who are Tomoro Coffee consumers in Sumbawa. The analytical technique used is multiple linear regression to measure the partial influence of each variable. The results show that all three variables, Product, Price, and Place, have a positive and significant effect on purchase decisions. Among them, Price has the strongest influence, followed by Place and Product. These findings offer strategic implications for F&B businesses in designing effective marketing mixes in regional markets and emphasize the importance of perceived quality, price affordability, and outlet location in shaping consumer purchase decisions. Additionally, this study contributes to the marketing management literature by providing empirical insights from a non-metropolitan area in Indonesia.